Spatial Distributions, Characteristics, and Applications of Craniofacial Stem Cells - Geru Zhang; Qiwen Li; Quan Yuan; Shiwen Zhang (Hindawi Limited, 2020)
Stem cells play an irreplaceable role in the development, homeostasis, and regeneration of the craniofacial bone. Multiple populations of tissue-resident craniofacial skeletal stem cells have been identified in different stem cell niches, including the cranial periosteum, jawbone marrow, temporomandibular joint, cranial sutures, and periodontium. These cells exhibit self-renewal and multidirectional differentiation abilities. Here, we summarized the properties of craniofacial skeletal stem cells, based on their spatial distribution. Specifically, we focused on the in vivo genetic fate mapping of stem cells, by exploring specific stem cell markers and observing their lineage commitment in both the homeostatic and regenerative states. Finally, we discussed their application in regenerative medicine.